2021
DOI: 10.1177/01945998211045292
|View full text |Cite
|
Sign up to set email alerts
|

Autologous Adipose Tissue Injection of Vocal Cords in Presbyphonia

Abstract: Objective This series evaluates the long-term results of autologous adipose injection (AAI) in patients older than 65 years with presbyphonia. Study Design Retrospective cohort study. Setting Academic secondary medical center. Methods This was a retrospective study with a minimum follow-up of 12 months. All patients underwent AAI for atrophy of both vocal folds due to presbyphonia. We measured subjective parameters as Voice Handicap Index–10 (VHI-10) or GRBAS scale (grade, roughness, breathiness, asthenia, str… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(1 citation statement)
references
References 50 publications
0
1
0
Order By: Relevance
“…Kwon et al ( 48 ) reported that 12 months after injection laryngoplasty with calcium hydroxyapatite, patients showed improvement in both subjective and objective voice measurements. González-Herranz et al ( 49 ) found that elderly patients treated with autologous adipose tissue for presbyphonia had improvement in Voice Handicap Index-10 outcomes, maximum phonation time, and GRBAS scale during a mean 22.89-month follow-up. Another method, as a durable treatment option, for glottic incompetence is type I (medialization) thyroplasty which needs to be performed in an operating theater under local anesthesia in patients with larger glottic gap or those who did not sufficiently benefit from voice therapy or injection laryngoplasty ( 8 , 47 ).…”
Section: Surgerymentioning
confidence: 99%
“…Kwon et al ( 48 ) reported that 12 months after injection laryngoplasty with calcium hydroxyapatite, patients showed improvement in both subjective and objective voice measurements. González-Herranz et al ( 49 ) found that elderly patients treated with autologous adipose tissue for presbyphonia had improvement in Voice Handicap Index-10 outcomes, maximum phonation time, and GRBAS scale during a mean 22.89-month follow-up. Another method, as a durable treatment option, for glottic incompetence is type I (medialization) thyroplasty which needs to be performed in an operating theater under local anesthesia in patients with larger glottic gap or those who did not sufficiently benefit from voice therapy or injection laryngoplasty ( 8 , 47 ).…”
Section: Surgerymentioning
confidence: 99%